Surgery on a Galapagos Giant Tortoise - Tapia, Raul (My University, 2015)
The purpose of this research was to document the surgery of a 50 year old female Galapagos giant tortoise who had been injured by a car.
Color poster with text and photographs.
Keywords: Galapagos; Giant tortoise; Veterinary surgery; Posters